THE INFLUENCE OF WORKLOAD AND INDIVIDUAL CHARACTERISTICS ON THE PERFORMANCE OF NURSES IN BUMI MASSENREMPULU GENERAL HOSPITAL, ENREKANG DISTRICT THROUGH BURNOUT AS AN INTERVENING VARIABLE - Abdul Halid Latif; Idayanti Nursyamsi; Andi Nur Baumassepe (Journal of Accounting Issues, 2023)
The purpose of this study was to provide an overview of how the influence of workload and individual characteristics on the performance of nurses at the Bumi Massenrempulu General Hospital, Enrekang Regency, through burnout as an intervening variable. This research is categorized as explanative research using a quantitative approach. This is intended to be able to describe or describe in a systematic, factual and accurate manner the object under study. Descriptive research with a quantitative approach aims to describe systematically and analytically about the characteristics of an individual, symptom, condition or certain groups between a symptom and other symptoms in society. The results of this study are: 1) Workload has an effect on burnout, this proves that a high workload will increase burnout, this is indicated by the path coefficient value of 0.288 and the t-statistic value of 2.815. This value is greater than t-table (1.983); 2) Individual characteristics affect burnout, this proves that having high individual characteristics will increase burnout, this is indicated by the path coefficient value of 0.521 and the t-statistic value of 6.525. This value is greater than t-table (1.983); 3) Workload affects performance, this proves that a high workload can also improve nurse performance, this is indicated by the path coefficient value of 0.388 and the t-statistic value of 3.803. This value is greater than t-table (1.983); 4) Individual characteristics do not affect performance, this proves that high individual characteristics will not always improve nurse performance, this is indicated by the path coefficient value of 0.118 and the t-statistic value of 1.137. This value is smaller than t-table (1.983); 5) Burnout affects performance, this proves that high burnout will reduce nurse performance, this is indicated by the path coefficient value of 0.629 and the t-statistic value of 6.091. This value is greater than t-table (1.983); 6) Workload has an indirect effect on performance through burnout, if the workload is high it will improve the performance of nurses if there is a change in burnout in a more positive or better direction, this is indicated by the path coefficient value of 0.181 and the t-statistic value of 2.889. This value is greater than t-table (1.983); 8) Individual characteristics have an indirect effect on performance through burnout, if individual characteristics are high it will improve nurse performance if there is a change in burnout in a more positive or better direction, this is indicated by the path coefficient value of 0.327 and the t-statistic value of 3.935 . This value is greater than t-table (1.983). 983); 8) Individual characteristics have an indirect effect on performance through burnout, if individual characteristics are high it will improve nurse performance if there is a change in burnout in a more positive or better direction, this is indicated by the path coefficient value of 0.327 and the t-statistic value of 3.935 . This value is greater than t-table (1.983). 983); 8) Individual characteristics have an indirect effect on performance through burnout, if individual characteristics are high it will improve nurse performance if there is a change in burnout in a more positive or better direction, this is indicated by the path coefficient value of 0.327 and the t-statistic value of 3.935 . This value is greater than t-table (1.983).